2022
DOI: 10.1136/rmdopen-2022-002672
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated long non-coding RNA in Sjögren’s disease impacts both interferon and adaptive immune responses

Abstract: ObjectiveSjögren’s disease (SjD) is an autoimmune disease characterised by inflammatory destruction of exocrine glands. Patients with autoantibodies to Ro/SSA (SjDRo+) exhibit more severe disease. Long non-coding RNAs (lncRNAs) are a functionally diverse class of non-protein-coding RNAs whose role in autoimmune disease pathology has not been well characterised.MethodsWhole blood RNA-sequencing (RNA-seq) was performed on SjD cases (n=23 Ro/SSA negative (SjDRo−); n=27 Ro/SSA positive (SjDRo+) and healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…Linc01871, a lncRNA expressed in mature CD4+ and CD8+ T cells, class-switched memory B cells, plasma cells, natural killer cells, and hematopoietic progenitor cells was upregulated in SjD Ro + and SjD Ro − subgroups, with the highest expression found in the SjD Ro − patients. Linc1871 was induced by interferon (IFN)-γ in Kasumi 3 (early myeloid) cells and regulated by calcineurin and TCR signaling in primary human T cells [61]. The expression of OAS123-AS1, MX1-AS1, GBP5-AS1, and NRIR was increased in SjD Ro + patients but not in the SjD Ro − subgroup [61], in line with the established higher IFN signatures in SjD Ro + patients [62].…”
Section: Long Non-coding Rnas As Biomarkersmentioning
confidence: 71%
See 2 more Smart Citations
“…Linc01871, a lncRNA expressed in mature CD4+ and CD8+ T cells, class-switched memory B cells, plasma cells, natural killer cells, and hematopoietic progenitor cells was upregulated in SjD Ro + and SjD Ro − subgroups, with the highest expression found in the SjD Ro − patients. Linc1871 was induced by interferon (IFN)-γ in Kasumi 3 (early myeloid) cells and regulated by calcineurin and TCR signaling in primary human T cells [61]. The expression of OAS123-AS1, MX1-AS1, GBP5-AS1, and NRIR was increased in SjD Ro + patients but not in the SjD Ro − subgroup [61], in line with the established higher IFN signatures in SjD Ro + patients [62].…”
Section: Long Non-coding Rnas As Biomarkersmentioning
confidence: 71%
“…At least some of the differences observed might be based on altered immune cell composition, which was addressed by the authors using a deconvolution analysis. Most cell types were similarly distributed among the two SjD subgroups and healthy controls, with the exception of M2 macrophages, which were increased in both SjD subgroups; monocytes were increased and CD4+ T cells were decreased in the SjD Ro + group [61]. Linc01871, a lncRNA expressed in mature CD4+ and CD8+ T cells, class-switched memory B cells, plasma cells, natural killer cells, and hematopoietic progenitor cells was upregulated in SjD Ro + and SjD Ro − subgroups, with the highest expression found in the SjD Ro − patients.…”
Section: Long Non-coding Rnas As Biomarkersmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, although KLRC1 and KLRD1 form the inhibitory NKG2A/CD94 receptor, their expression on otherwise activated T-cells is shown only to limit excessive activation to sustain immune response 18 . Further, expanded clonotypes are expressed (i) under influence of LINC01871 , associated with TCR-dependent cytotoxicity in Sjogren’s disease 19 , (ii) on a subset of T-cells expressing two TCRαβ, associated with auto-and allo-cross-reactivities 14 , and (iii) in the same pathogenic cluster as diverse polyclonal T-cells, with a more limited but nonetheless cytolytic signature consistent with antigen-induced activation 15 . These data support a ‘selective-signaling’ model of TCR-triggered activation whereby different clonotypes support proliferation and/or cytolytic secretion.…”
Section: Mainmentioning
confidence: 99%
“…However, no association between serological markers of SS and expression levels of MALAT1 were found, which was thought to be due to the small sample size [ 57 ]. Joachims et al reported the overexpression of lncRNA LINC01871 in patients with SS, suggesting that LINC01871 dysregulates T cell-mediated inflammatory pathways in SS [ 58 ]. Considering the knowledge introduced in this section, it was presumed that various lncRNAs differentially expressed in blood samples from patients with SS participated the pathophysiology of SS, the mechanism of which were in part in association with IFN-α.…”
Section: The Involvement Of Long-noncoding Rnas In Ssmentioning
confidence: 99%